Albani Inconsistency in Assessing The Quality of Rawi Hadith in The Book Irwā' Al-Galīl - Muhammad Rafi'iy Rahim; Mohamad Syafri (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2022)
Many figures in the field of Hadith science, including contemporary hadith figures, who tries to do an in-depth study. One who is considered as a prominent hadith figure in this modern age is al-Albani. In several of his books, al-Albani applies several methods that are considered by some to be new methods. One of Al-Albani's phenomenal books, Irwā al-Galīl fī Manār al-Sabīl, has become a reference for scholars who studies him. This study focuses on Al-Albani's method in determining status of rawi in the book Irwā al-Galīl fī Manār al-Sabīl. Using the qualitative method, within the framework of the design of the critique of Al-Albani's work. This study examines 2,707 hadiths contained in the book. This study finds that Al-Albani in the book often shows an inconsistent attitude in determining the status of a hadith rawi. The form of this inconsistency is found in the changing attitudes of Al-Albani in determining the status of several narrators, including Al-Sa'q bin Hazn, 'Aqil bin Mudrik, Mujja'ah bin Al-Zubair, Harun bin Antarah, 'Amr bin Malik, and 'Amr bin Abd Al-Rahman. From the results of the research found, a general conclusion can be drawn, that Al-Albani at Irwā al-Galīl fī Manār al-Sabīl still shows an inconsistent attitude, especially in determining the status of a narrator.